In vitro and in vivo evaluation of the antimalarial MMV665831 and structural analogs. Issue 17 (1st September 2020) - Ding, Sha; Fike, Katherine R.; Klemba, Michael; Carlier, Paul R.
Graphical abstract: Abstract: Antimalarial candidates possessing novel mechanisms of action are needed to control drug resistant Plasmodium falciparum . We were drawn to Malaria Box compound 1 (MMV665831) by virtue of its excellent in vitro potency, and twelve analogs were prepared to probe its structure–activity relationship. Modulation of the diethyl amino group was fruitful, producing compound 25, which was twice as potent as 1 against cultured parasites. Efforts were made to modify the phenolic Mannich base functionality of 1, to prevent formation of a reactive quinone methide. Homologated analog 28 had reduced potency relative to 1, but still inhibited growth with EC50  ≤ 200 nM. Thus, the antimalarial activity of 1 does not derive from quinone methide formation. Chemical stability studies on dimethyl analog 2 showed remarkable hydrolytic stability of both the phenolic Mannich base and ethyl ester moieties, and 1 was evaluated for in vivo efficacy in P. berghei -infected mice (40 mg/kg, oral). Unfortunately, no reduction in parasitemia was seen relative to control. These results are discussed in the context of measured plasma and hepatocyte stabilities, with reference to structurally-related, orally-efficacious antimalarials.